AN ATTEMPT TO HISTORICALLY TRACING THE EMERGENCE OF THE VOCAL GROUP IN AN EXTRACURRICULAR ENVIRONMENT - Batkova, Anastasia (E-Journal VFU, 2025)
The vocal group in an extracurricular environment is one of the most widespread forms of musical education nowadays. Interest in vocal groups continues to grow more and more, today they are “modern”, but along with this, questions also appear – where, how and why they arose, what is their origin. In this presentation, an attempt is made to trace some historical and social reasons that led to the emergence of the vocal group in an extracurricular environment and explain its relevance today.
Keywords: vocal group; extracurricular activities; musical education